TensorFlow Reinforcement Learning Quick Start Guide: Get up and Running with Training and Deploying Intelligent, Self-Learning Agents Using Python - Balakrishnan, Kaushik (Packt Publishing, Limited, 2019)
This book is an essential guide for anyone interested in Reinforcement Learning. The book provides an actionable reference for Reinforcement Learning algorithms and their applications using TensorFlow and Python. It will help readers leverage the power of algorithms such as Deep Q-Network (DQN), Deep Deterministic Policy Gradients (DDPG), and.